2017
DOI: 10.1080/10408398.2017.1378865
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maillard reaction products on nutrition and health: Current knowledge and need to understand their fate in the human digestive system

Abstract: The Maillard Reaction (MR) is a non-enzymatic chemical reaction which results in the linkage between the amino group of amino acids and the carbonyl group of reduced sugars. MR products (MRPs) are common components of processed foods, mainly as a result of heating, especially in the Western diet. MRPs are classified as into three stages: initial, intermediate, and final stages, indicative of increased complexity and size, incurring different flavor, aroma, and texture. MRPs presence is known to reduce the nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
96
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 151 publications
0
96
0
1
Order By: Relevance
“…In contrast with other Maillard reaction products (MRP), melanoidins are generally considered to be harmless, and even potentially beneficial to human health [8]. Though some studies reported that dietary melanoidins might display moderate genotoxicity and cytotoxicity effects [9,10], several studies reported potential health benefits, including antioxidant, antihypertensive, antimicrobial, and prebiotic properties of food melanoidins [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with other Maillard reaction products (MRP), melanoidins are generally considered to be harmless, and even potentially beneficial to human health [8]. Though some studies reported that dietary melanoidins might display moderate genotoxicity and cytotoxicity effects [9,10], several studies reported potential health benefits, including antioxidant, antihypertensive, antimicrobial, and prebiotic properties of food melanoidins [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…LG-oleic acid-3 generated via oxidation of Amadori product during Maillard reaction and originated from glucose through dehydration, isomerization and retro-aldolization. [23][24][25] In addition, as shortchain a-dicarbonyl compounds, GO and MGO can also be generated from lipid oxidation reactions involving free radicals. 26 They can also undergo Strecker degradation to form aldehydes that play a key role in color and avor formation.…”
Section: Effects Of Fatty Acids and Triglycerides On The Formation Ofmentioning
confidence: 99%
“…45 It was reported that the acidity of the systems could impact the chemical fate of fructoselysine, which might be responsible for the more pyrraline formation from non-oxidative degradation with addition of fatty acids. 23 But it is noteworthy that further study is needed to clarify the involving rationale. The concentration of pyrraline raised up with the increase of fatty acid content, which may have been a result of an increased acidication of the model systems.…”
Section: Effects Of Fatty Acids and Triglycerides On Pyrraline Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of HMF is widely used as a parameter to asses honey freshness and appropriate storage conditions (2). It is also ubiquitous in the human diet and is present in high concentrations in processed foods and foodstuffs as a result of heating, roasting, frying and toasting (3). HMF concentration is greater than 1 g/kg in dried fruits, caramel products and some fruit juices and up to 6.2 g/kg in instant coffee (4).…”
mentioning
confidence: 99%